San Marino : Financial Sector Assessment Program-Technical Note on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2010)
The level of domestically generated proceeds of serious crime in San Marino is low. However, San Marino is vulnerable to money laundering (ML) of proceeds of crimes committed abroad. The Sammarinese financial sector, until recently, was characterized by a number of features that have created a favorable environment to ML. San Marino has made considerable progress in bringing its legal and institutional framework in line with the Financial Action Task Force (FATF) recommendations. Banks and financial institutions have started implementing the new Antimoney Laundering and Combating the Financing of Terrorism (AML/CFT) requirements, with mixed results.